2010
DOI: 10.1159/000324910
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Brain Arteriovenous Malformations in Children: Correlation of Clinical Outcome with Admission Parameters

Abstract: Aims: To gain a better understanding of how clinical outcome in children with ruptured brain arteriovenous malformations (bAVMs) correlates with clinical and imaging parameters on admission. Methods: The authors retrospectively reviewed patients with bAVMs, aged 18 or below, managed at their hospital between January 1992 and December 2008. Clinical outcome was assessed using the modified Rankin Scale (mRS). Patients with ruptured bAVMs were analyzed; their clinical parameters and computerized tomography findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Although this study has quite impressive follow-up (mean 9.2 years), there was a remarkably high complication rate with treatment of highgrade (Grade IV and V) AVMs (28% compared with 5% in low-grade lesions), although this was accounted for in multivariate modeling. Wong et al 28 analyzed mRS clinical outcomes at 6 months and "most recently" in a series of 40 treated pediatric bAVMs. They found Spetzler-Martin grade, intracerebral hemorrhage score, WFNS SAH grade, and GCS scores all to be predictive of clinical outcome (mRS score) at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study has quite impressive follow-up (mean 9.2 years), there was a remarkably high complication rate with treatment of highgrade (Grade IV and V) AVMs (28% compared with 5% in low-grade lesions), although this was accounted for in multivariate modeling. Wong et al 28 analyzed mRS clinical outcomes at 6 months and "most recently" in a series of 40 treated pediatric bAVMs. They found Spetzler-Martin grade, intracerebral hemorrhage score, WFNS SAH grade, and GCS scores all to be predictive of clinical outcome (mRS score) at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Initial research identified 70 eligible articles and included 15 articles 1,2,11,16,17,20,35,46,47,51,53,59,62,66,76 that described any factors associated with hemorrhagic presentation, after excluding 55 articles for the following reasons: no data for calculating the risk of variables for hemorrhagic presentation, 22,44,58,63,64,75,79,83 inclusion of the same cohort as another report, 48,69 patients with AVMs treated before hemorrhage, 14,49,51,55,74 inclusion of only specific cases (such as patients with hereditary hemorrhagic telangiectasia, 78 cerebellar AVM, 25 Gamma Knife surgery, 4,6-8, 13, 15, 24, 27, 34, 38, 40, 54, 57, 60, 70,80-82 embolization, 12,67 or microsurgery 18,23,26,43 treatment), impossibility of separating pediatric patients from adult patients, 10,28,33,41,45,77 less than 20 cases included,…”
Section: Literature Searchmentioning
confidence: 99%
“…Figure 2 illustrates two preterm infants born at 29 weeks gestational age (GA) with small CBHs ( 61 ). Wong and Fong ( 62 ) investigated children with ruptured brain arteriovenous malformations and employed multivariate analyses which demonstrated that a scoring scale that combined the Glasgow Coma Score, pupillary response and significant focal neurological injuries was a statistically significant independent predictor of clinical outcomes 6 months after hemorrhage.…”
Section: Resultsmentioning
confidence: 99%